Light on snow : a novel - Shreve, Anita (New York : Little, Brown and Company, 2004)
When a father and his daughter find an abandoned infant in the snow, the event forever alters the 11-year-old's understanding of the world.
Keywords: Abandoned children -- New England -- Fiction; Domestic fiction